1999
DOI: 10.1211/0022357991772790
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and the Central Nervous System: from Forgotten Factors to Potent Anxiolytic Compounds

Abstract: The list of activities of plant flavonoids did not include effects on the central nervous system (CNS) up to 1990, when our laboratory described the existence of natural anxiolytic flavonoids. The first of these was chrysin (5,7-dihydroxyflavone), followed by apigenin (5,7,4'-trihydroxyflavone) and flavone itself. Semisynthetic derivatives of flavone obtained by introducing halogens, nitro groups or both in its molecule, give rise to high affinity ligands for the benzodiazepine receptor, active in-vivo; 6,3'-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 45 publications
3
99
1
Order By: Relevance
“…Pomegranate leaves contain unique tannins such as punicalin and punicafolin, and also have glycosides of apigenin, a flavone with progestinic (Zand et al, 2000) and anxiolytic (Paladini et al, 1999) properties. Pomegranate peel are rich in hydrolyzable tannins, mainly punicalin, pedunculagin, and punicalagin , which differ from proanthocyanidins in their chemical structures.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Pomegranate leaves contain unique tannins such as punicalin and punicafolin, and also have glycosides of apigenin, a flavone with progestinic (Zand et al, 2000) and anxiolytic (Paladini et al, 1999) properties. Pomegranate peel are rich in hydrolyzable tannins, mainly punicalin, pedunculagin, and punicalagin , which differ from proanthocyanidins in their chemical structures.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Other authors reported beneficial effects of G. biloba extract against beta-amyloid-mediated neurotoxicity in primary hippocampal neurons [11,57] and implicated antioxidant activities and the modulation of intracellular calcium levels in PC12 cells [209] as possible mechanisms of action. Other lines of research focused on the binding of flavonoids such as apigenin, naringenin, kaempferol, quercetin-3-O-glucoside and others to benzodiazepine binding sites [149] of different receptors including the GABA-A-receptor [52,132] and adenosine receptors [139], and investigated their anxiolytic potential [149] as a possible mechanism of action in the CNS. Bastianetto et al report that antioxidant effects are not the only mechanism of flavonoid-mediated protection against neuronal death and show attenuation of NO • -induced activation of protein kinase C (PKC) by G. biloba [12] and resveratrol [13] to be partially involved in the protection against neurotoxicity.…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…They are important constituents of the human diet [2] and can also be found in expressive amounts in many medicinal plants [3]. Amongst the wide range of biological and pharmacological properties of these compounds we find a series of reports on their activity in the central nervous system (CNS) (for reviews see [4][5][6]). Since the discovery that certain flavonoids (namely flavones) specifically recognise the central BDZ receptors [7,8], efforts have been made to identify naturally occurring GABA A receptor benzodiazepine binding site ligands [5] to understand their interaction with these receptors [9][10][11][12] and to establish the CNS activity of different natural [13] and synthetic flavonoids [14,15].…”
Section: Introductionmentioning
confidence: 99%